RCAPChA: RSU controlled AHP-based prioritised channel allocation protocol for hybrid VANETs. (7th July 2022) - Bhabani, Bidisha; Mahapatro, Judhistir
Restricted geographical scope and bounded time relevance are two main attributes of emergency/non-emergency messages in VANETs. Therefore, a suitable medium access control (MAC) protocol is required explicitly for VANETs which can deliver timely and reliably these messages. However, channel-allocation remains a challenging problem in VANETs. In this paper, we propose an algorithm RCAPChA which minimises waiting time of the most deserving vehicle by prioritising those vehicles which want to disseminate messages. RCAPChA uses a multi-criteria-based decision-making model named as analytic hierarchy process (AHP) and enables the RSU to rank the vehicles requesting for channels based on the calculated priority values involving three criteria which includes message type, vehicle speed, and channel occupancy time. Our simulation results show that RCAPChA performs better in minimising the overall delay for 60% of the deserving vehicles. It also defeats the existing schemes regarding delay, PSR, PDR and Throughput in saturated data traffic condition.